2021
DOI: 10.5539/jas.v13n4p15
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inoculum Concentration and Pretreatment on Biomethane Recovery From Cotton Gin Trash

Abstract: The potential of cotton gin waste, a considerable challenge to the gin owners, has not been fully investigated as a renewable energy source via anaerobic digestion. The weathered cotton gin trash and inoculum for triplicate biomethane potential assays were obtained from a local cotton gin mill and a municipal wastewater treatment plant, respectively. The moisture, total solids, volatile solids, and C, H, N, S, hemicellulose + cellulose, and lignin contents of gin waste were determined in triplicates. The biome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…These pre-treatments aim to loosen the cell walls of the recalcitrant plant components, such as lignin. In a previous study [41] we reported similar BMP values in control, hot water, and alkali pretreated CGT. The CGT in our study was collected from a pile outside the gin mill (weathered for more than 3 months).…”
Section: Cumulative Biomethane Production and Biodegradabilitysupporting
confidence: 71%
See 1 more Smart Citation
“…These pre-treatments aim to loosen the cell walls of the recalcitrant plant components, such as lignin. In a previous study [41] we reported similar BMP values in control, hot water, and alkali pretreated CGT. The CGT in our study was collected from a pile outside the gin mill (weathered for more than 3 months).…”
Section: Cumulative Biomethane Production and Biodegradabilitysupporting
confidence: 71%
“…The ISRs of 0.005, 0.007, 0.01, 0.02 and 0.04 (on VS basis) were tested on GM (unpublished data), and statistically similar yields were observed at ISRs of 0.005, 0.007, 0.01, 0.02 and 0.04. In our previous study [41], we reported that CGT yielded similar values of BMP at 0.02 and 0.03 ISRs. An equal (as that of inoculum) volume of trace medium [35] was added to each bioreactor.…”
Section: Biochemical Methane Potential Testsmentioning
confidence: 58%
“…Enrichment techniques have been widely used for the discovery and isolation of new microorganisms with desired abilities for given possible biotechnological applications. However, some factors are important concerning the enrichment, especially regarding the inoculum: the inoculum source [50,51], the inoculum age [52,53], the inoculum/substrate ratio [54][55][56][57], the preparation [58,59], and the new artificial conditions to which the inoculum will be submitted. Aeration is a well-known pretreatment method for the preparation of inocula for dark fermentation, as reviewed previously [60].…”
Section: Physical-chemical Characterization Of the Inoculum And Enric...mentioning
confidence: 99%
“…A total working volume of 100 mL in each treatment was achieved by adding deionized water (DI). Other procedures, including blanks, were the same as described in our previous studies [23,24,37]. More specifically, the blanks contained inoculum and all other ingredients except GM.…”
Section: Biomethane Potential Assaysmentioning
confidence: 99%
“…In addition to biomethane (carbon-neutral energy), the AD process produces less sludge, removes pathogens and odors more effectively, and yields digestate with high fertilizer value, thus having several advantages over aerobic digestion [19]. There are four major stages of the AD process, i.e., hydrolysis, acidogenesis, acetogenesis, and methanogenesis [20][21][22][23][24]. Gujer and Zehnder [25] identified six distinct processes: hydrolysis of biopolymers, fermentation of amino acids and sugars, anaerobic oxidation of long-chain fatty acids and alcohols, anaerobic oxidation of intermediate products such as volatile acids, conversion of acetate to methane, and conversion of hydrogen to methane occurring in the anaerobic digesters.…”
Section: Introductionmentioning
confidence: 99%